Can Mary Shelley's Frankenstein be read as an early research ethics text?. Issue 1 (10th June 2004) - Davies, H
Abstract : The current, popular view of the novel Frankenstein is that it describes the horrors consequent upon scientific experimentation; the pursuit of science leading inevitably to tragedy. In reality the importance of the book is far from this. Although the evil and tragedy resulting from one medical experiment are its theme, a critical and fair reading finds a more balanced view that includes science's potential to improve the human condition and reasons why such an experiment went awry. The author argues that Frankenstein is an early and balanced text on the ethics of research upon human subjects and that it provides insights that are as valid today as when the novel was written. As a narrative it provides a gripping story that merits careful analysis by those involved in medical research and its ethical review, and it is more enjoyable than many current textbooks! To support this thesis, the author will place the book in historical, scientific context, analyse it for lessons relevant to those involved in research ethics today, and then draw conclusions.